Creative Chemistry: Descriptive of Recent Achievements in the Chemical Industries - Slosson, Edwin E. (Edwin Emery), 1865-1929 (Salt Lake City, UT : Project Gutenberg, 2005)
"Creative Chemistry: Descriptive of Recent Achievements in the Chemical Industries" by Edwin E. Slosson is a scientific publication written in the early 20th century. This work explores various advancements and breakthroughs in the field of industrial chemistry, aiming to convey its significance and applications to a general audience. The book likely addresses topics such as the synthesis of new materials, chemical processes in agriculture, and the role of chemistry in wartime technologies. The opening of this volume sets the stage for discussing the transformative power of chemistry in human advancement. Slosson likens human progress to a journey through three distinct periods: the Appropriative Period, where raw materials are gathered; the Adaptive Period, characterized by improvements on found items; and the Creative Period, where new substances are synthesized through chemical processes. He emphasizes chemistry's role in both shaping industries and influencing life itself, while previewing the exploration of various innovations, such as the production of synthetic fertilizers and explosives driven by the demands of warfare. (This is an automatically generated summary.)
Release date is 2005-11-24
E-text prepared by Kevin Handy, John Hagerson, Josephine Paolucci, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Chemistry, Technical